Assessment of Debris Flow Activity in Response to an Earthquake Using the Sediment Connectivity Index - Li, Yanji; Hu, Kaiheng; Zhang, Xiaopeng; Hu, Xudong; Ning, Lan; Li, Hao (Frontiers in Earth Science, 2022)
Large earthquakes can trigger landslides and collapses, which not only increase the mass of loose solid materials but also change the topography of catchments. Debris flow activity in response to earthquakes is of widespread concern; however, most studies have focused on the material conditions and flow property variations prior to and after earthquakes. In this study, we investigate temporal variations in the debris flow activity in a typical catchment in the Wenchuan Earthquake area via the sediment connectivity index (IC), which reflects the sediment delivery efficiency in the catchment. The IC values in different tributaries and during different time periods were calculated to determine their spatial distribution and temporal variations. The results show that high IC values are distributed in downstream tributaries near the main fault. The IC values decreased significantly following a 2008 Wenchuan Earthquake, indicating a continuous decrease in the sediment transfer ability. The debris flow history and loose solid material amounts were also investigated via field surveys. The debris flow activity is closely related to variations in the solid material source amounts and the IC values in the catchment. This study provides a new insight into the assessment of debris flow activity with respect to its close relationship with the distribution of loose solid materials and the sediment connectivity.